NUMERICAL STUDY OF BIOCONVECTION AND CATTANEO-CHRISTOV HEAT FLUX MODEL IN MHD MAXWELL NANOFLUID FLOW OVER A VARIABLE THICKNESS ELASTIC SURFACE - Cao, Wenhao; Rehman, Saif Ur; Asjad, Muhammad Imran; İnç, Mustafa (Ministry Communications & High Technologies Republic Azerbaijan, 2024)
This study focuses on the boundary layer Maxwell nanofluid flow across a slender elastic surface of varying thickness. The Cattaneo-Christov heat flux model is utilized to investigate the heat transfer characteristics with variable thermal conductivity instead of the classical Fourier's law. This work is bioconvection caused by motivated and dynamic microorganisms for Maxwell nanofluid flow. The model's fundamental formulation is in PDEs, which are later converted to ODEs utilizing similarity variables. The Runge-Kutta method with a shooting technique is implemented in MATLAB to investigate the effects of varying different parameters on physically significant dependent variables. For different parameter values, representative results for velocity, temperature, nanoparticle concentration, and bioconvection profiles are shown in both graphical and tabular representations. The numerical outcomes are helpful in devising efficient heat exchangers for modern, complicated thermo-techno procedures in the industry, buildings, and transport sectors.
Keywords: Maxwell Nanofluid; Bioconvection; MHD; Slender Elastic Sheet; Cattaneo-Christove Heat Flux Model